Stress and job performance among non-academic staff at IIUM : a case study - Ramli (Institute of Education, International Islamic University Malaysia, 2013)
The purpose of this study is to review the reciprocal relationship between stress factors and job performance of selected non-academic staff of IIUM. Descriptive analysis, ANOVA and correlation statistics were administered in this study. Data were collected using scale of Job stress measured by a PerceivedStress Scale with the 14- items scale developed by Cohen. S, KamarckT,&Melmetstein (1983). The population of this study was 1161 of non-academic staff within nine facultiesof Gombak campus of IIUM. Using cluster sampling method, 103 of non- academic staff of IIUM were selected. The general findings regarding the perceived stress and job performance among the non-academic staff of IIUM is that, the majority of respondents believe that their present job is very convenient for them. Besides, there was no significant relationship found between stress factors and job performance, though the correlation between perceived stress and job performance was strong. On the issue of gender, age, and educational background among the non-academic staff of IIUM, the study revealed that there were no significant differences reported on those factors.